Who Knows? Reflexivity in Feminist Standpoint Theory and Bourdieu - Sweet, Paige L. (Gender & society, 2020)
Though the invocation to be “reflexive” is widespread in feminist sociology, many questions remain about what it means to “turn back” and resituate our work—about how to engage with research subjects’ visions of the world and with our own theoretical models. Rather than a superficial rehearsal of researcher and interlocutor standpoints, I argue that “reflexivity” should help researchers theorize the social world in relational ways. To make this claim, I draw together the insights of feminist standpoint theory and Bourdieu’s reflexive sociology to lay the foundation for a renewed reflexive project that centers epistemic privilege, the idea that positions of structural exclusion provide the best resources for theorizing social power. Reflexive sociology should consider interlocutors’ experiences of exclusion and contradiction, engaging with sites of alternative knowledge and incorporating them into the object of study. This type of reflexivity provides improved resources for relational theory building. I offer support for these theoretical arguments with a historical analysis of knowledge production in the feminist anti-violence movement.